Theory of Organization and New Institutionalism in Organizational Analysis - de la Rosa Alburquerque, Ayuzabet (Administración y Organizaciones, 2025)
This article deals with the theoretical implications of New Institutionalism in organizational analysis. To show it, the importance of studying organizations and institutions is briefly exposed. Organization Theory and its most recent developments are revised and its principal neo-institutionalism points. Afterward, based on the previous facts, New Institutionalism theoretical argumentative links are established concerning Organization Theory. Finally, the limits and contributions of New Institutionalism for the organizational analysis are analyzed and possible research lines are suggested.